2004
DOI: 10.1111/j.1432-2277.2004.tb00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Aminopyrine breath test compared to the MELD and Child-Pugh scores for predicting mortality among cirrhotic patients awaiting liver transplantation

Abstract: Better tools for predicting the risk of death while awaiting transplantation are urgently needed because organ shortage is increasing the numbers on transplantation waiting lists. The aminopyrine breath test (ABT), model for endstage liver disease (MELD), and Child-Pugh (C-P) score were compared as predictors of this risk in 137 cirrhotic candidates for liver transplantation. Eighty-three were transplanted within 3 months of registration, 35 others survived, 13 died before transplantation, and 6 were removed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
5
12
2
1
Order By: Relevance
“…Nonetheless, for the assessment of individuals at the bedside, it can be anticipated that Child-Pugh will resist as an almost intuitive score which can be combined easily with other clinical information. [48] 2003 Cirrhosis, LT 3437 3-month mortality 0.76 0.83 Degré D et al [50] 2004 Cirrhosis, LT 137 3-month mortality 0.72 0.70 Said A et al [30] 2004 Chronic liver diseases 1611 3-year mortality 0.83 0.79 Concordance (c) statistic represents the area under receiving-operating-characteristic (ROC) curve, plotting sensitivity against 1-specificity. This statistic, ranging from 0 to 1, is an global marker of the validity of the score for predicting the event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, for the assessment of individuals at the bedside, it can be anticipated that Child-Pugh will resist as an almost intuitive score which can be combined easily with other clinical information. [48] 2003 Cirrhosis, LT 3437 3-month mortality 0.76 0.83 Degré D et al [50] 2004 Cirrhosis, LT 137 3-month mortality 0.72 0.70 Said A et al [30] 2004 Chronic liver diseases 1611 3-year mortality 0.83 0.79 Concordance (c) statistic represents the area under receiving-operating-characteristic (ROC) curve, plotting sensitivity against 1-specificity. This statistic, ranging from 0 to 1, is an global marker of the validity of the score for predicting the event.…”
Section: Discussionmentioning
confidence: 99%
“…A surprising finding is that despite MELD score represents a determinant progress in terms of methodology and validation, its accuracy for predicting outcome in cirrhotic patients, as shown in Table 4, is not always superior (and may even be inferior) to that of Child score [49,50]. Receiving-operating-characteristic (ROC) curve and the derived c statistic provide a global and standardized appreciation of the accuracy of a marker or a composite score for predicting an event.…”
Section: Child or Meld?mentioning
confidence: 95%
“…This underlines the fact that the critical threshold may be lower for HCC than for patients with cirrhosis without HCC, for whom the CTP has been estimated at 11. 26 It must be emphasized that for our patients listed for HCC and not for end-stage liver disease, the MELD score was not a predictive factor of LTX failure, when competing with the CTP score in the multivariate analysis. Moreover, it was not statistically significant (P ϭ 0.67; data not shown) in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The breath test had a high prognostic value for survival and short-term survival [q = 0.73 (95% CI 0.66-0.81)], and correlated with the Child-Pugh score better than with the MELD-score (q = 0.72 and q = 0.60 respectively). Degre et al (45) further showed that the 13 C 2 -aminopyrine breath test has a greater area under curve than both the Child-Pugh and the MELD scores in cirrhotic patients awaiting transplantation, suggesting that the breath test is as good as or better in predicting mortality. In post-transplantation settings, the combination of the 13 C 2 -aminopyrine and the 13 C-methionine breath test (for mitochondrial function) could be used to evaluate the functioning of the orthotopic transplant liver to predict graft outcome (40).…”
Section: Studies Of the 13 C 2 -Aminopyrine Breath Testmentioning
confidence: 99%